Pakistan Development Policy Review : A New Dawn? - World Bank (Washington, DC, 2013)
This Development Policy Review describes, and evaluates the Government of Pakistan's policies, in six critical areas : governance, investing in people, macroeconomic sustainability, the financial sector, the investment climate for the private sector, and, agriculture and irrigation. Governance reforms are aimed at addressing four major issues: devolution, civil service reform, reduction of corruption and improvement of financial management, and institutionalizing realistic budget processes. On investing in people, the social gap (reinforced by gender discrepancies) show high illiteracy, and ill-health rates, which limits the possibilities for economic growth. To this end, spending commitments prioritize on social sectors, and effective service delivery. As for macroeconomic sustainability, the unsustainable public debt poses a serious problem, exacerbated by defense spending, which diminishes development expenditure. This challenges the move of public debt dynamics towards improving the investment climate, through increased tax revenue, and limiting defense expenditure. The financial sector is dominated by the banking system, where state-owned institutions play a significant role, which despite progress, much needs to be done in strengthening prudential regulations, and capital markets. Concurrently, the unstable investment climate requires a regulatory framework in terms of taxes, and tariffs. Finally, policy priorities are required to accelerate agricultural growth on markets, technology, and irrigation.